1997
DOI: 10.1007/s004210050319
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tourniquet ischemia for strength training with low resistance

Abstract: To investigate the efficacy of ischemia in strength training with low mechanical stress, tourniquet ischemia was utilized in low-resistance training. Five untrained subjects conducted one-legged isometric knee extension training with one leg ischemic (I-leg) and the other non-ischemic (NI-leg). Repeated isometric contractions for 2 s with 3 s relaxation in between were continued for 3 min and conducted 3 days/week for 4 weeks as training. Training resistance was 40% of maximal voluntary contraction (MVC) of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
160
5
14

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(183 citation statements)
references
References 6 publications
4
160
5
14
Order By: Relevance
“…The BFR technique generally involves application of a tourniquet [34], inflatable cuff [35] or elastic knee wraps [36] at the top of each arm or leg to restrict blood flow into the muscle, and occlude blood flow out of the muscle. While elastic automated cuff systems have been developed and popularized in Japan, it may be more practical to employ inflatable cuffs or simple elastic wraps, particularly when large groups are performing BFR.…”
Section: Type Of Cuffmentioning
confidence: 99%
“…The BFR technique generally involves application of a tourniquet [34], inflatable cuff [35] or elastic knee wraps [36] at the top of each arm or leg to restrict blood flow into the muscle, and occlude blood flow out of the muscle. While elastic automated cuff systems have been developed and popularized in Japan, it may be more practical to employ inflatable cuffs or simple elastic wraps, particularly when large groups are performing BFR.…”
Section: Type Of Cuffmentioning
confidence: 99%
“…The BFR technique involves application of a tourniquet [14], inflatable cuff [18] or elastic knee wraps [19] around the proximal end of a limb to occlude distal blood flow, thus inducing a localized hypoxic environment during exercise [20]. Early research utilized occlusive pressures in excess of 200 mmHg [8], though more recent findings have demonstrated beneficial results with pressures as low as 50 mmHg [21].…”
Section: Resistance Exercise With Blood Flow Restrictionmentioning
confidence: 99%
“…Training with BFR (also known as Kaatsu training) is currently promoted as a novel training method that enhances muscle hypertrophy and strength [22]. While the American College of Sports Medicine typically recommends that resistance training intensity exceed 60% 1-repetition maximum (1RM) to induce optimum hypertrophy [23], numerous studies have demonstrated substantial increases in hypertrophy and strength following [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] weeks of BFR training at intensities as low as 20% 1RM [21,[24][25][26]. Although the precise mechanisms are not yet clear, the augmented responses to resistance exercise with BFR are believed to be accounted for by a greater accumulation of metabolites and concomitant increases in anabolic hormone concentrations, intramuscular signalling, intracellular swelling and motor unit recruitment [8,12,18].…”
Section: Resistance Exercise With Blood Flow Restrictionmentioning
confidence: 99%
See 2 more Smart Citations